Pengaruh Aplikasi Pupuk Organik Plus Pada Bawang Merah (Allium ascalonicum) terhadap Keanekaragaman Arthropoda di Lahan Gambut - Oktaviani, Yerenia Teresa; Pramudi, Muhammad Indar; ., Salamiah (www.ulm.ac.id, 2024)
Shallots (Allium ascalonicum L.) from the Lilyceae family are annual horticultural plants. The aim of this research is to determine the effect of the application of organic fertilizer plus on the diversity of arthropods in shallot plants in peatlands. The method used in this research was a one-factor Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. Data from arthropod identification results are grouped based on order and family which are presented in tabular form. Then an analysis was carried out using diversity indices, species richness and species evenness. The results of the research show that the most dominant arthropods are the predator group. The results also show that the level of arthropod species diversity is moderate, the level of arthropod species richness is low, the level of evenness of arthropod species shows an unstable distribution. The most dominant group of arthropods is the predator group and the results of the LSD analysis test at the 5% level showed a real influence on the diversity of arthropods in shallot plants in peatlands where organic fertilizer plus 125 g/hole was applied with an average of 48.40 individuals.